Bing-Neel Syndrome: Real-Life Experience in Personalized Diagnostic Approach and Treatment - Kotsos, Dimitrios; Chatzileontiadou, Sofia; Apsemidou, Athanasia; Xanthopoulou, Anna; Rapi, Aikaterini; Frouzaki, Christina; Hatjiharissi, Evdoxia (Frontiers in Oncology, 2022)
The involvement of the central nervous system (CNS) in Waldenström’s Macroglobulinemia (WM) is a rare extramedullary manifestation of the disease known as Bing-Neel syndrome (BNS). To expand our understanding of this disease manifestation, we conducted a retrospective analysis of the incidence of BNS in 86 consecutive patients with WM [70% male, median age 65 years (range 33-86 years)] seen in our center during a 30-year period. Six patients (7%) from this group were diagnosed with BNS. The median period of time between WM diagnosis and BNS diagnosis was 6.8 years (range 2,3-15). They demonstrated a range of neurological deficits, including transient expressive aphasia, impaired vision, resting hand tremor, foot drop, and headache. The diagnosis was made not on the basis of neurological symptoms or radiological evidence, but on the basis of the presence of WM cells in cerebrospinal fluid (CSF). Intrathecal chemotherapy with methotrexate, cytarabine, and dexamethasone (IT MTX, ARA-C, DEX) was used as front-line treatment, followed by intensive immunochemotherapy with rituximab, high-dose MTX, and ARA-C (R-Hi MTX/ARA-C) in three patients who were fit enough to receive this type of cytotoxic regimen, and rituximab plus bendamustine (R-Benda) in two patients who simultaneously required treatment for WM. Ibrutinib was administered to five patients (three as consolidation and two for initial treatment). All patients responded to front-line treatment, with four (67%) achieving PR and two (33%) achieving CR. This study provides insight into the clinical presentation, diagnostic and treatment options, and also the outcome of patients who have BNS.